Temporary partnerships as an information transmission mechanism: foreign investment in emerging markets - H. Peter Møllgaard; Per Baltzer Overgaard (Copenhagen Business School (CBS), Department of Economics, 1998)
Asymmetric information and fear of acquiring a 'lemon' may explain the paucity of foreign investment in emerging market economies. If investors are uncertain about the profitability of investments, intrinsically inefficient, temporary partnerships or joint ventures may serve as mechanisms through which information is transmitted. Temporary partnerships with joint in- vestments by the domestic firm and the foreign investor, together with a buy-out option to the investor, can be used to separate good and bad invest- ment prospects in equilibrium. However, non-revealing equilibria may exist. Implications for foreign direct investment are traced and briefly related to the experience of transition economies.
hdl:10398/7496
Keywords: D8; F2; L14; O12; 330; investment; complementary assets; partnerships; joint ventures and licensing; costly signaling